Using Numbered Head Together Technique on Students’ Reading Comprehension - nurdiana nurdiana (Indonesian Journal of Integrated English Language Teaching, 2016)
In increasing students’ reading comprehension, various techniques have been applied by the lecturer. However, based on the preliminary study, it was found that the students have low comprehension in reading, including the narrative text. Numbered head together technique was offered to improve students’ reading comprehension. The purpose of the research were to investigate the difference of students’ reading comprehension on narrative text before and after  being taught by using Numbered Head Together Technique and to investigate the effect of using Numbered Head Together Technique toward students’ reading comprehension of narrative text at the English Education Department of UIN Suska Riau.The research design was quasi experimental research. The population was the third semester students of English Education Department of UIN Suska Riau. Two groups which consisted of 55 students were invited to be samples by using cluster-random sampling. Both groups were administered the pretest and the posttest. The technique of collecting data used test. The technique of data analysis used was paired sample t test. The research found that there was significant difference of students’ reading comprehension on narrative text after being taught by using numbered head together technique for experimental class and non-treatment of numbered head together technique for control class. It was stated by the value of sig. (2-tailed) was 0,000. It was smaller than 0,05. It meant that the use of Numbered head together technique had a significant effect on students’ reading comprehension on narrative text.